The Effect Of Tourist Experience And Travel Motivation On Revisit Intention At Goa Lawah Natural Tourism, West Lombok Regency - Juandika Setiananda; Lalu Muhammad Furkan (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of tourist experience and travel motivation on revisit intention among tourists at Goa Lawah Nature Tourism, West Lombok Regency. This research employs a quantitative approach with an associative research design involving 100 respondents who are tourists who have previously visited Goa Lawah Nature Tourism, West Lombok Regency. The sampling technique used was purposive sampling, and the data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results show that tourist experience has a positive and significant effect on revisit intention, with a coefficient of 0.516, a t-statistic value of 5.433, and a p-value of 0.000. In addition, travel motivation also has a positive and significant effect on revisit intention, with a coefficient of 0.417, a t-statistic value of 3.965, and a p-value of 0.000. These findings indicate that enjoyable, comfortable, and memorable tourism experiences, as well as tourists’ motivation for relaxation, entertainment, and seeking new experiences, play an important role in encouraging revisit intention. Therefore, improving the quality of tourist experiences and fulfilling tourists’ travel motivations are key strategies to enhance tourist loyalty and ensure the sustainability of Goa Lawah Nature Tourism in West Lombok Regency